391 Effects of increasing carbohydrases levels on productive performance of beef cattle fed feedlot finishing diets. (5th December 2019) - Carvalho, Victor V; Perdigão, Alexandre; Acedo, Tiago S; Vasconcellos, Guilherme S; Tamassia, Luis Fernando
Abstract: Our objective was to evaluate the effects of feeding increasing exogenous carbohydrases levels on cattleˈ performance, when fed a 90-d feedlot finishing diet. A total of 240 Nellore bulls (IBW = 389 ± 27 kg) were distributed in 24 pens (10 animals/pen), in a randomized complete block design (6 pens/treatment). The basal diet was composed by 15% sugarcane bagasse, 72.8% ground corn, 7.6% soybean meal and 4.6 % mineral-vitamin premix (DM basis). The treatments were: 1) control: No addition of carbohydrases blend; 2) Blend1, in g/animal/d: 1 g of Ronozyme ® WX (xylanase) + 3.75 g of Ronzyme ® VP (beta-glucanase); 3) Blend2, in g/animal/d: 2 g of Ronozyme ® WX + 7.5 g of Ronzyme ® VP and 4) Blend3, in g/animal/d: 4 g of Ronozyme ® WX + 15 g of Ronzyme ® VP. The animals were fed once a day and had free access to fresh water. Statistical analysis was performed using the MIXED procedure of SAS 9.4, and comparisons were performed out by orthogonal contrasts, which compared the control and treatments, and the linear and quadratic effects of the increasing carbohydrases levels. Statistical significance was declared at P < 0.05, and tendencies considered when 0.05 < P < 0.10. Animals fed carbohydrases had greater (P = 0.045) ADG (1.59 vs. 1.51 kg/d) and tended to have greater (P = 0.069) final BW (533.4 vs. 527.7 kg) compared with control; although no difference were observed on these variables among carbohydrases levels. Feeding carbohydrases increased DM intake, expressed either as kg/d (10.17 vs. 9.92; P = 0.019) and as percentage of BW (2.20 vs. 2.16 %; P = 0.038), compared to control group, respectively. However, no difference was observed among treatments on G:F, and dressing percentage. In conclusion, the addition of carbohydrases blend can improve performance of finishing cattle.